Identification of a specific limitation on local-feedback recurrent networks acting as Mealy-Moore machines - Kremer, S.C. (IEEE transactions on neural networks, 1999)
Describes a proof which identifies limitations of local-feedback recurrent networks (LFRNs) in representing Mealy-Moore machines. Specifically, the paper identifies a class of machines that are unrepresentable in these networks. While it is known that LFRNs cannot represent all automata, this is the first paper to show a specific class of unrepresentable automata. The paper goes beyond previous work in the area by addressing realistic activation functions, arbitrary network architectures, and more general computing machines.